2022
DOI: 10.3390/jrfm15030102
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mandatory Audit Firm Rotation on Earnings Management and Audit Fees: Evidence from Iran

Abstract: The present study aims to investigate the effects of mandatory requirements of audit firm rotation on earnings management among companies listed on the Tehran Stock Exchange (TSE). The study population consists of 1030 observations and 103 companies listed on the TSE during the years 2003–2012; moreover, the statistical technique used to test the hypotheses is panel data and pooled data. The results showed that the rule of mandatory audit firm rotation increased accruals-based earnings management (AEM) signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…The SNA change ( SNA_AUDCH) is not effectively restraining EM practices, as reported in regressions 35 to 40, as displayed in Table 12. These results are in line with the study of Salehi et al (2022), which found that audit firm rotation (switch) did not have any significant influence on EM. According to Salehi et al (2022), audit firm rotation is not a deterrent to EM when firms face financial distress.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The SNA change ( SNA_AUDCH) is not effectively restraining EM practices, as reported in regressions 35 to 40, as displayed in Table 12. These results are in line with the study of Salehi et al (2022), which found that audit firm rotation (switch) did not have any significant influence on EM. According to Salehi et al (2022), audit firm rotation is not a deterrent to EM when firms face financial distress.…”
Section: Resultssupporting
confidence: 91%
“…These results are in line with the study of Salehi et al (2022), which found that audit firm rotation (switch) did not have any significant influence on EM. According to Salehi et al (2022), audit firm rotation is not a deterrent to EM when firms face financial distress.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…While longer auditor tenure may help auditors become more familiar with their clients' operations and thus improve the quality of their audits, it can also result in closer, more amicable relationships with management, potentially compromising auditor independence (Chi et al, 2011). This has given rise to two opposing points of view regarding auditor rotation, with its supporters and detractors (Salehi et al, 2022).…”
Section: Auditor Tenure and Emmentioning
confidence: 99%
“…The scientific literature offers a large number of studies that focus on external threats to independence, especially on the effect of rotations and audit fees (Duong Thi, 2023;Gandía & Huguet, 2018;Lohwasser & Zhou, 2023;Nekhili et al, 2022;Salehi et al, 2022;Usman et al, 2022), with inconclusive results. Some authors, such as Zgarni et al (2016), Choi et al (2022b) and Hoang et al (2022), have even focused on analyzing these threats within the so-called Big Four accounting firms.…”
Section: Introductionmentioning
confidence: 99%